1991
DOI: 10.1002/aja.1001910202
|View full text |Cite
|
Sign up to set email alerts
|

Liver units in three dimensions: I. organization of argyrophilic connective tissue skeleton in porcine Liver with particular reference to the “compound hepatic lobule”

Abstract: Liver units were investigated in pig livers by means of histologic serial tracing, physical model building, and computer-aided three-dimensional imaging. Observations of the argyrophilic connective tissue skeleton were based mainly on the celloidin-embedded serial sections treated with silver impregnation. The parenchymal mass that clothed the initial segments of hepatic venous radicles was demarcated by fibrous septa which formed isolable units with two basic patterns: the simple hepatic lobule (SHL) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 70 publications
1
56
0
1
Order By: Relevance
“…The fundamental problem might be the larger size of the pig liver, in which case clinical application will need to take this unavoidable factor into account. However, the pig liver is known to have an unusual connective tissue framework, with a distinct collagen lattice around each hepatic lobule, 19 a characteristic not seen in rodents or man. If this is the fundamental problem, then our study and other studies [15][16][17] in pigs might underestimate the effectiveness of the hydrodynamic procedure in man.…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental problem might be the larger size of the pig liver, in which case clinical application will need to take this unavoidable factor into account. However, the pig liver is known to have an unusual connective tissue framework, with a distinct collagen lattice around each hepatic lobule, 19 a characteristic not seen in rodents or man. If this is the fundamental problem, then our study and other studies [15][16][17] in pigs might underestimate the effectiveness of the hydrodynamic procedure in man.…”
Section: Discussionmentioning
confidence: 99%
“…Complex CVs are comprised of the hepatic vein together with many small branches connected directly with sinusoids. In human 29 and pig 30 livers, sinusoids enter only the smallest branches of hepatic veins. In addition, CVs in the rat (Figs.…”
Section: Difference In Lobular Angioarchitecture Of the Normal Rat Anmentioning
confidence: 99%
“…Intrahepatic termination of the arteria hepatica propria has been a controversial issue for more than a century. 1 Review of the literature shows that the subject became controversial in 1866, when Chrzonszczewsky, 2 with his classic experiments of selective ligation and injection, observed that branches of the hepatic artery penetrated into the depth of the lobule, and concluded subsequently that the artery nourished the central half of the liver lobule, whereas the portal vein supplied the peripheral half. One hundred years later, in 1966, not only were the statements unsupported, but also many studies extended the controversy about the anatomy [3][4][5][6][7] and physiology 8,9 of intrahepatic arterial distribution.…”
mentioning
confidence: 99%